Search Light : Consciousness at the Millennium - Barlett, Mark; Buchman, Lorne M.; Chalmers, David J.; Churchland, Paul M.; Crick, Francis; Hayward, Jeremy W.; James, William; Jamme, Franck Andre; Koch, Christof; Kolpan, Steve; Lakoff, George; Nagel, Thomas; et al. (New York : Thames & Hudson, 1999)
Bacher, Lutz ; Barry, Robert ; Beckett, Samuel ; Bourgeois, Louise ; Cha, Theresa Hak Kyung ; Creed, Martin ; Davé, Cristabel ; Douglas, Stan ; Eshkar, Shelley ; Gordon, Douglas ; Graham, Rodney ; Hannah, David ; Herold, Jörg ; Hill, Gary ; Irwin, Robert ; Keiser, Paul ; Martin, Agnes ; Ono, Yoko ; Oppenheim, Kristin ; Piper, Adrian ; Raetz, Markus ; Reinhardt, Ad ; Sherman, Stuart ; Stidworthy, Imogen ; Thater, Diana ; Tompkins, Rosie Lee ; Viola, Bill ; Wearing, Gillian ; Wiedemann, Pascale ; Young, La Monte ; Zazeela, Marian
Searchlight: Consciousness at the Millennium, opening September 1999 at the California College of Arts and Crafts, San Francisco
Engels
boek